Detection of HIV-1 and Human Proteins in Urinary Extracellular Vesicles from HIV+ Patients - Samuel I. Anyanwu; Akins Doherty; Michael D. Powell; Chamberlain Obialo; Ming B. Huang; Alexander Quarshie; Claudette Mitchell; Khalid Bashir; Gale W. Newman (Advances in Virology)
Background. Extracellular vesicles (EVs) are membrane bound, secreted by cells, and detected in bodily fluids, including urine, and contain proteins, RNA, and DNA. Our goal was to identify HIV and human proteins (HPs) in urinary EVs from HIV+ patients and compare them to HIV− samples. Methods. Urine samples were collected from HIV+ (n=35) and HIV− (n=12) individuals. EVs were isolated by ultrafiltration and characterized using transmission electron microscopy, tandem mass spectrometry (LC/MS/MS), and nanoparticle tracking analysis (NTA). Western blots confirmed the presence of HIV proteins. Gene ontology (GO) analysis was performed using FunRich and HIV Human Interaction database (HHID). Results. EVs from urine were 30–400 nm in size. More EVs were in HIV+ patients, P<0.05, by NTA. HIV+ samples had 14,475 HPs using LC/MS/MS, while only 111 were in HIV−. HPs in the EVs were of exosomal origin. LC/MS/MS showed all HIV+ samples contained at least one HIV protein. GO analysis showed differences in proteins between HIV+ and HIV− samples and more than 50% of the published HPs in the HHID interacted with EV HIV proteins. Conclusion. Differences in the proteomic profile of EVs from HIV+ versus HIV− samples were found. HIV and HPs in EVs could be used to detect infection and/or diagnose HIV disease syndromes.